Low-Cost Solutions Using the Infrastructure as a Service with High Availability and Virtualization Model - Moreira Zambrano, Cesar Armando; Zambrano-Romero, Walter Daniel; Guamán-Quinché, Rene; Cuenca Álava, Wilner Geoberti (Enfoque UTE, 2017)
This paper presents the results obtained from the implementation of an infrastructure to improve technological services of email, virtual learning environment, digital repository and virtual library at the Polytechnic Agricultural Higher School of Manabí (Polytechnic School of Agriculture of Manabí), ESPAM, through the use of high availability and virtualization mechanisms to provide more reliable resources. Virtualization is an empowering and cutting-edge technology that is transforming the operation of technological services, but it involves a paradigm shift in serviceoriented information technologies and cloud computing. To execute each of the processes the V-cycle methodology was used as a strategy. Virtualization services empowers companies and institutions by transforming how they operate to be at the forefront of innovation in their services as a technological solution. So the implementation of redundant technology in the ESPAM, has allowed its technological services are always operative, for the benefit of the university community, because if there were failures in the main system or services, the backups will be enabled quickly allowing the systems come into operation immediately.